PENGARUH PELATIHAN BUDAYA SADAR BENCANA TERHADAP PERILAKU KESIAPSIAGAAN BENCANA KEBAKARAN PADA REMAJA (DI KELURAHAN GEDONGOMBO KECAMATAN SEMANDING KABUPATEN TUBAN): The Impact of Disaster Awareness Training on Fire Disaster Preparedness Behavior Among Adolescents (In Gedongombo Village, Semanding Subdistrict, Tuban Regency - Prasetyo, Afif Singgih; Ferianto, kusno; Lukman Hakim (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Behavior is a form of deed or activity performed by the individual in his or her daily life that can be observed directly or not, such as walking, speaking, crying, laughing, writing, reading, and so on. Teeneger is one of the nation's assets that are vulnerable to disasters and there is no readiness in the face of disaster. However, based on the youth experience in Gedongombo Village, there has been no socialization of disaster preparedness training. This research aims to know the influence of disaster-conscious cultural training on the behavior of fire disaster preparedness in teenegers in Gedongombo Village Semanding Subdistric. The research method used is pre-experimental, with the design of one group pre-use-test design. The population in this study consisted of 19 adolescents in Gedongombo Village. The research sample consisted of 18 teenegers from Gedongombo Village selected by simple random sampling. The instrument used was the SOP disaster and preparedness behavior questionnaire sheet. It was found that most of the behavior of teenegers preparedness in the face of a fire disaster before being given the training of disaster-conscious culture, the behavior of poorly prepared behaviors, and after the training was given the disaster-conscious culture of most of the already-prepared behavior. The result The statistical test showed that there is an influence of disaster-conscious cultural training on the behavior of fire disaster preparedness in teenegers in the village Gedongombo Semanding Subdistrict with a value of use-value = 0.000 at α = 0.05 (P < 0.05). Therefore, it can be concluded that H1 is accepted. Expected disaster- conscious culture training can improve the behavior of adolescent preparedness in the face of a fire disaster and can apply in case of fire. Keywords: Disaster-conscious Cultural Training; Fire Disaster; Teenegers Preparedness Behavior